2020
DOI: 10.1002/anie.202006943
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Through‐Space Substituent Effects

Abstract: The description of substituents as electron donating or withdrawing leads to a perceived dominance of through‐bond influences. The situation is compounded by the challenge of separating through‐bond and through‐space contributions. Here, we probe the experimental significance of through‐space substituent effects in molecular interactions and reaction kinetics. Conformational equilibrium constants were transposed onto the Hammett substituent constant scale revealing dominant through‐space substituent effects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 86 publications
1
27
0
Order By: Relevance
“… 28 Around the same time, Cockroft and co-workers performed a set of elegant experiments to probe the relative significance of through-bond and through-space substituent effects in molecular interactions and reaction kinetics. 29 The resulting data clearly revealed dominant through-space interactions for the considered systems; in fact, it turned out that, depending on the precise spatial orientation of specific substituents, their classically assigned electron-donating/electron-withdrawing character could be turned off – or even reversed altogether.…”
Section: Introductionmentioning
confidence: 94%
“… 28 Around the same time, Cockroft and co-workers performed a set of elegant experiments to probe the relative significance of through-bond and through-space substituent effects in molecular interactions and reaction kinetics. 29 The resulting data clearly revealed dominant through-space interactions for the considered systems; in fact, it turned out that, depending on the precise spatial orientation of specific substituents, their classically assigned electron-donating/electron-withdrawing character could be turned off – or even reversed altogether.…”
Section: Introductionmentioning
confidence: 94%
“…Substituent effects on aromatic interactions have been successfully correlated with the substituent Hammett σ parameter for many different systems [6, 10, 11, 26–30] . The value of σ quantifies the overall effect of a substituent on the electronic properties of an aromatic ring, including both through‐space electrostatic effects and through‐bond resonance and inductive effects [31, 32] . An analysis of substituent effects on bicyclo[2.2.2]octane‐1‐carboxylic acids showed that electric field effects in non‐aromatic systems are also well‐described by the Hammett σ m parameter [33] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 , 10 , 11 , 26 , 27 , 28 , 29 , 30 ] The value of σ quantifies the overall effect of a substituent on the electronic properties of an aromatic ring, including both through‐space electrostatic effects and through‐bond resonance and inductive effects. [ 31 , 32 ] An analysis of substituent effects on bicyclo[2.2.2]octane‐1‐carboxylic acids showed that electric field effects in non‐aromatic systems are also well‐described by the Hammett σ m parameter. [33] Here we use a Hammett analysis of substituent effects on aromatic stacking interactions to extrapolate the electrostatic contributions to zero and thereby measure the residual non‐polar contribution to the total interaction energy.…”
Section: Introductionmentioning
confidence: 99%
“…[64,65] The efficacy of both methods in rationalizing reactivity trends supports that both electrostatic and inductive contributions are active, and methods to distinguish between these contributions are still being pursued to this day. [66] Obtaining a more detailed understanding of the relative magnitude of inductive and electrostatic factors would be valuable, particularly as leveraging through-space interactions should serve as an ideal strategy to break free-energy relationships. [67][68][69][70][71][72][73] Phosphines are ideal scaffolds to quantify the influence of electrostatics as these ligands feature prominently in catalysis and have well defined parameters for their donor strength such as the Tolman Electronic Parameter (TEP).…”
Section: Introductionmentioning
confidence: 99%